Strategies and Rules of Doing Business at ‘Rostagroexport’ Group of Companies - A. V. Butov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides history of setting up the company 'Rostagroexport', one of the biggest producer of dairy produce in Russia. The author shows in detail the evolution of the group strategy development, from aggressive dumping to output of premium produce and offer of exclusive services (sports and recreation) and describes preconditions of their development and conditions of implementation, as well as specific features of designing polar strategies supplementing key lines in the group activity, which are typical of the period of corporate maturity. In its speedy development the group successively passed over from strategy of cost leadership to strategy of vertical integration and differentiation and later to strategy of diversification by minimizing risks, optimizing various business-processes, extending its production and trading potential, creating inter-branch cooperation, including enterprises of agriculture, food industry and trade, sports and tourist sphere, etc. An important place in the article is taken by analyzing rules of doing business, i.e. grounds of efficient management of any enterprise developed by B. Alexandrov, the founder of the group as a result of long experience of developing different corporate businesses and a comparative analysis of 'Rostagroexport' group rules with management principles of other well-known entrepreneurs and their companies. On this basis advantages and shortcomings of their use in management of commercial organizations of a wide sphere of activity were identified. Special attention is paid to study and assessment of such socially important rules of doing business, as 'pay to your employees in good time' and 'motivate people in positive ways'.